Clinical features and outcomes in pediatric patients with cortical laminar necrosis: a single-center retrospective study - Zhanwei Zhang; Zou Pan; Lifen Yang; Fang He; Fangyun Liu; Jing Peng (Italian Journal of Pediatrics)
Abstract Background Cortical laminar necrosis (CLN) is a selective cortical necrosis primarily involving layer 3 of the cortex. Its causes, clinical features, and outcomes in pediatric patients remain unclear due to limited cases. Methods Pediatric CLN patients from Xiangya Hospital from January 2014 to December 2024 were enrolled. Clinical data, brain magnetic resonance imaging (MRI), and Modified Rankin Scale (mRS) for neurological outcomes were analyzed. Results Among 59 enrolled patients, causes included hypoxic-ischemic encephalopathy (HIE), hereditary and metabolic, infectious, vascular, and trauma. Seizures and consciousness changes were common symptoms. Infectious and hereditary and metabolic causes were linked to status epilepticus (P < 0.001), while vascular causes were associated with hemiplegia (P < 0.001). HIE patients had poorer prognosis (P = 0.038). MRI showed earlier hyperintensity on diffusion weighted imaging (DWI) than enhancement in T1 contrasted sequence, as well as T1 sequence and fluid attenuated inversion recovery (FLAIR). Bilateral involvement was seen in all HIE cases, while hereditary and metabolic causes often showed unilateral involvement (P < 0.001). Frontal lobe involvement was common in vascular and trauma cases (P = 0.017), and all patients with HIE exhibited involvement in the parietal and occipital lobes. While infectious cases frequently involved the insular and temporal lobes, most patients exhibited brain atrophy/encephalomalacia at follow-up. Three patients showed new CLN and two patients exhibited persistent CLN during MRI follow-up. Conclusion HIE, hereditary/metabolic, infectious, vascular, and trauma are the main causes of pediatric CLN, with distinct clinical features and outcomes.